(3GdYdGbI Hjf GdQYGjI GdegfjI hGdEdJRGe GdJfXjei (B: s (3eY OQGSI JWHjbjI Ydi GdYGedjf HGdeQcR GdQFjSi ai GdHfc GdCgdi GdeUQi (B/ s - (3MfGf jhSa Ydi eSYhOs; (3YGdjI YHOGdMejO YGQa (B: s ((3GdbGgQI (B: s (3MfGf jhSa Ydi eSYhO (B: s, 2014)
(3JfHY CgejI GdOQGSI ef JfGhdgG CMO eaGgje GdJWhjQ GdEOGQi hgh eaghe GdQYGjI GdegfjI (B: (3ceG JSYi GdOQGSI deYQaI eOi JWHjb eaghe GdQYGjI ai GdefXeGJ GdeUQajI ai eUQ (B: (3hJMOjO eJWdHGJ GdJWHjb heRGjG heYhbGJ GdJWHjb (B. (3hbOeJ GdOQGSI EWGQkG ddYdGbI eG Hjf GdQYGjI GdegfjI hGdEdJRGe GdJfXjei HeG jSGYO Ydi RjGOI eSJhi GdEdJRGe GdJfXjei ef NdGd eONd GdQYGjI GdegfjI (B. (3hNdUJ GdOQSI dVQhQI JhGaQ YOO ef GdeJWdHGJ dJWHjb YedjI GdQYGjI GdegfjI hCgegG JhGaQ bjGOI EOGQjI JJHfi YedjI GdQYGjI (B: (3ai Xd fXGe LjO ddEJUGdGJ hKbGaI JfXjejI OGYeI heSGfOI dYedjI GdQYGjI(B. (3hbO CXgQJ GdOQGSI Cf dgPg GdeJWdHGJ JCKjQ eHGTQ Ydi GdEdJRGe GdJfXjei hCf GdYGedjf HGdhXGFa GdETQGajI ai GdeQcR GdQFjSi ai GdHfc GdCgdi GdeUQi dOjge OQLI YGdjI ef GdESJYOGO ddYed cQYGI (B. (3ceG Cf GdYGedjf HGdhXGFa GdfeWjI dOjge OQLI YGdjI ef GdEdJRGe GdJfXjei Ydi GdQZe ef YOe TYhQge HGdQYGjI GdegfjI HGdbOQ GdcGais
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdEbJUGO h GdYdhe GdSjGSjI (B- (3bSe GdEOGQI GdYGeIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdEdJRGe GdJfXjeis; (3GdOYe Gdegfis; (3GdQYGjI GdegfjIs